Remdesivir (GS-5734) for COVID-19 Treatment: Past and Recent Updates - Arul, Santhosh; Dayalan, Haripriya (Coronaviruses, 2021)
Background: SARS-CoV-2 is a pandemic now, and several measures have been taken by countries to prevent, control, and treat the disease. WHO has been working meticulously and has been providing up to date information and statistics on incidences and death. Several broad- -spectrum anti-viral drugs are available and have been used in the past to fight against the viral outbreak. Recently remdesivir, an experimental prodrug from Gilead Sciences, has been found to be a potential drug to be used as a therapy to treat COVID-19. Objective: Here, we have reviewed several previous findings from the literature and present an up to date information on remdesivir. Result: Remdesivir was initially invented for use against Ebola virus treatment and has proved effective against different strains of Ebola, Nipah, and other strains of coronaviruses. Clinical trials with remdesivir for COVID-19 patients have begun, and several off label use of remdesivir have been reported recently. Currently, the drug seems to have an effect against the SARS-CoV-2 virus, with side effects among a few patients. Although the results are not conclusive, they are partly promising. This review provides past and recent updates on the use of remdesivir. Conclusion: From the review, we conclude that the drug remdesivir is known to exhibit its mechanism of action by terminating the RNA synthesis, and it is a potential drug against the novel coronavirus.
Keywords: SARS-CoV-2